Study of oat malt influence on butter biscuit structuring - Skrypko, Anhelina; Kyianytsia, Svetlana; Obolkina, Vera; Yemelyanova, Nina (My University, 2013)
Improving technology butter cookie with a high content of essential amino acids, macro-and micronutrients and other bioactive components. Adding malt flour contribute to the accumulation of maltose and glucose through hydrolysis of starch under the action of amylolytic enzymes, which can reduce the sugar content in pastry products. Удосконалення технології здобного печива з підвищеним вмістом незамінних амінокислот, макро- та мікронутрієнтів, інших біологічно-активних компонентів. Додавання солодового борошна сприятиме накопиченню мальтози і глюкози завдяки гідролізу крохмалю під дією амілолітичних ферментів, що дозволяє зменшити вміст цукру в борошняних кондитерських виробах
Keywords: wheat flour; unfermented flour with oat malt; oat meal; борошно пшеничне; борошно з неферментованого вівсяного солоду; вівсяне борошно; мука пшеничная; мука из неферментированного овсяного солода; овсяная мука; кафедра технології хлібопекарських і кондитерських виробів